2007
DOI: 10.1007/s00227-007-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of the azooxanthellate coral Tubastraea coccinea in the Equatorial Eastern Pacific: Part V. Dendrophylliidae

Abstract: The reproductive ecology of Tubastraea coccinea Lesson, an azooxanthellate tropical scleractinian coral, was studied over various periods from 1985 to 2006 at four principal eastern PaciWc locations in Costa Rica, Panamá, and the Galápagos Islands (Ecuador). This small (polyp diameter 0.8-1.0 cm), relatively cryptic species produced ova and planulae year round, including colonies with as few as 2-10 polyps. Of 424 colonies examined histologically, 13.7% contained both ova and sperm. Mature ova varied in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 39 publications
2
46
0
6
Order By: Relevance
“…In fact, planulae usually settle and metamorphose within a relatively brief period of time, around 3 d (Glynn et al 2008), probably favoring self-recruitment and promoting the gregarious spatial pattern often reported for this species (e.g., Paula and Creed 2005;Glynn et al 2008). However, we observed that alternative developmental pathways are possible in T. coccinea.…”
Section: Introductionmentioning
confidence: 81%
“…In fact, planulae usually settle and metamorphose within a relatively brief period of time, around 3 d (Glynn et al 2008), probably favoring self-recruitment and promoting the gregarious spatial pattern often reported for this species (e.g., Paula and Creed 2005;Glynn et al 2008). However, we observed that alternative developmental pathways are possible in T. coccinea.…”
Section: Introductionmentioning
confidence: 81%
“…It is a hermaphroditic brooder and reproduces by producing planulae year-round (Glynn et al 2008a). Egg development requires 6 to 8 wk.…”
Section: Introductionmentioning
confidence: 99%
“…The native range of the sun coral Tubastraea coccinea Lesson comprises the Pacific and Indian Ocean (Cairns, 2000), but this species has been introduced in shallow tropical habitats at many locations worldwide (Glynn et al, 2008), including the southeastern Brazilian coast (da Silva and Barros, 2011;Ferreira, 2003;Mantelatto et al, 2011;Paula and Creed, 2005). The rapid invasion of T. coccinea in this region is likely due to the expansion of the oil industry and associated shipping activity (Ferreira, 2003;Paula and Creed, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, larvae of several azooxanthellate coral species, including T. coccinea, concentrate in downward facing (negative) and vertical surfaces, or crevices, where they can find release from competition with fast-growing coral species that use symbiont microalgae and light as an energy source (Bak and Engel, 1979;Birkeland, 1977;Fenner and Banks, 2004;Ferreira, 2003;Glynn et al, 2008;Lewis, 1974;Rogers et al, 1984;Vermeij, 2005). In the case of invading species, information on larval substrate selection is particularly important to establish environmental policies to help control their spread and understand potential effects on native communities.…”
Section: Introductionmentioning
confidence: 99%